Utilisation of recycled aggregate as coarse aggregate in concrete - Yong, P.C; Razali, I.; Teo, DCL (Universiti Malaysia Sarawak, (UNIMAS), 2009)
In this research, recycled concrete aggregates (RCA) from site-tested concrete specimens were used. These consist of 28-days concrete cubes after compression test obtained from a local construction site. These concrete cubes are crushed to suitable size and reused as recycled coarse aggregate. The amount of recycled concrete aggregate used in this research is approximately 200 kg.